XPS and UV\x96vis studies of Ga-doped zinc oxide nanoparticles synthesized by gelatin based sol-gel approach - Khorsand Zak, A. (Elsevier Ltd, 2016)
Undoped and gallium-doped ZnO nanoparticles, (ZnO NPs) (Zn1−xGaxO, x=0.0, 0.03, 0.06, 0.09, 0.12, 0.15), were synthesized by a gelatin-based, sol–gel method. Structural and morphological studies of the resulting products were carried out via X-ray diffraction analysis (XRD) and transmission electron microscopy (TEM). The XRD results revealed that the sample products were crystalline with a hexagonal wurtzite phase. Furthermore, the TEM images indicated ZnO NPs having approximately spherical shapes, with their particle size distributed over the nanometer range. The XRD and TEM results also showed a decrease in crystallite and particle sizes of NPs from x=0.0 to 0.15. The size-strain plot (SSP) method was employed to study the individual contributions of crystallite sizes and lattice strain to the peak broadening of the undoped and doped ZnO NPs. The effect of doping on the optical band-gap and crystalline quality was also investigated, using ultraviolet-visible (UV–vis), X-ray photoluminescence (XPS), and spectroscopies of the pure and doped ZnO NPs. It was observed that the band-gap and O-vacancies of the doped ZnO NPs were red-shifted in comparison with those of the undoped ZnO NPs in UV–vis and XPS results.